Dampak Variasi Model Propagasi Terhadap Protokol Routing Reaktif, Proaktif, dan Hybrid di Jaringan VANET (Studi Kasus Kota Bima) - Nazibullah Nazibullah; Andy Hidayat Jatmika; Fitri Bimantoro (Program Studi Teknik Informatika, Fakultas Teknik, Universitas Mataram, 2021)
VANET is a subset of Mobile Adhoc Network (MANET) that utilizes wireless technology, which in the VANET network the node is presented as a vehicle and the route for a vehicle is presented as a highway that will be passed by that vehicle. In general, VANET has 3 classification routing protocols, namely reactive, proactive, and hybrid. Performance of routing protocol is greatly influenced by the propagation model. Propagation on the network is the behavior of radio waves, which in this case is used as a transmission medium from the transmitter to the destination (receiver). This research will analyze the variation of propagation models namely FreeSpace, TwoRayGround, Shadowing, and Nakagami on the performance of AOMDV (reactive), OLSR (proactive), and ZRP (hybrid). The performance of the routing protocol will be tested using test parameters including Packet Delivery Ratio (PDR), Packet Loss, End to End Delay, and Throughput. Keywords: VANET, AOMDV, OLSR, ZRP, FreeSpace, TwoRayGround, Shadowing, Nakagami